Artikel Review : Evaluasi Peran Eksipien Dalam Meningkatkan Stabilitas Sediaan Farmasi - Talitha salshabilla Azzahra (Jurnal Farmasi Sains dan Teknologi, 2026)
Tablet stability is an important factor affecting the quality, safety, and effectiveness of pharmaceutical preparations. Excipients play a major role in maintaining the physical and chemical stability of tablets. This study aimed to evaluate the role of excipients in improving tablet stability through a literature review using scientific articles published from 2016–2026. The data were analyzed descriptively by comparing the effects of various excipients on tablet stability. The results showed that excipients such as HPMC, HPC, xanthan gum, sucrose, and mannitol improved the stability of lozenges by increasing hardness and reducing friability. In effervescent tablets, citric acid, tartaric acid, sodium bicarbonate, and PEG enhanced dissolution but reduced mechanical stability due to their hygroscopic properties. Overall, lozenges showed better stability than effervescent tablets. Therefore, appropriate excipient selection is essential to produce stable and high-quality tablet formulations.